BPJS Kesehatan Deactivation Policies: An Online Media Content Analysis in Indonesia - Eka Putri Rahayu; Riyan Ningsih; Dian Ardyanti (Universitas Mulawarman, 2026)
The issue of membership deactivation intensified markedly in early 2026 when the Indonesian government announced the deactivation of health insurance coverage for approximately 11 million recipients of government-subsidized contributions (PBI BPJS) as of February 1, 2026. Understanding how the BPJS Kesehatan deactivation policy is framed across prominent online media platforms is therefore a matter of both academic and policy significance. This study was a qualitative study of online news portal content that aims to evaluate the discourse surrounding the deactivation policy of BPJS Kesehatan in Indonesia. The research sample consists of national online media news about BPJS Kesehatan deactivation policy published January 1, 2026 until April 30, 2026. The researcher used the keyword “BPJS non aktif” and searched five online news portals. MAXQDA software was also used as a data analysis tool in this study. Features used included Word Cloud and word frequency to understand the main concepts. The results showed that there were six dominant topics in the coverage of well-known online media in Indonesia related to BPJS Kesehatan deactivation policy. The topic of partial solution was the most dominant topic with 26 quotes.